2018
DOI: 10.3390/atmos9090358
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally-Related Cherry Root Cambial Plasticity

Abstract: The general aim of this research was to determine whether the cherry root cambium possesses similar water-stress adaptation abilities as the scion. Specifically, this study aimed to determine whether there is a shift in root xylem structure due to precipitation fluctuations and temperature increase during the growing season in two cherry species. Oblačinska sour cherry and European ground cherry roots with secondary structure were anatomically surveyed in detail, and correlated with meteorological conditions o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Since investigated stems were of the same age, sampled from the same part of the plant and grown in the same environmental setting, SDs are presumed to be strongly genetically dependent as previously noted for eucalyptus (Bartholomé et al, 2020). High heritability and genetic control of anatomical traits and water use efficiency was previously noted by Lauri et al (2011) as well as Lopez et al (2017). Lesser variation in CSA was observed in scion stems in comparison with the rootstock stems, indicating that to some extent scion retains its scionspecific cambial activity.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…Since investigated stems were of the same age, sampled from the same part of the plant and grown in the same environmental setting, SDs are presumed to be strongly genetically dependent as previously noted for eucalyptus (Bartholomé et al, 2020). High heritability and genetic control of anatomical traits and water use efficiency was previously noted by Lauri et al (2011) as well as Lopez et al (2017). Lesser variation in CSA was observed in scion stems in comparison with the rootstock stems, indicating that to some extent scion retains its scionspecific cambial activity.…”
Section: Discussionmentioning
confidence: 59%
“…Thus, higher V e of trees on P. cerasus rootstock candidates in comparison with control trees could be due to higher susceptibility of trees on 'Gisela 5' to water scarcity during the drought events, which might have resulted in suppressed tree growth. Since 'Gisela 5' is considered as low-vigour inducing (Lang, 2000), our results showed that all investigated rootstock candidates are potentially dwarfing.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations